Free Cash Flow, Signaling and the Dividend Puzzle - Alan V. Douglas (Queen's University, Department of Economics, 1990)
The work in this paper contributes to two of the most topical issues in the study of corporate financial policy: Free Cash Flow theory and the Dividend providing a new explanation for the dividend puzzle. It is argued that two types of asymmetric information problems are inherent in the relationship between shareholders (as principles) and managers (as the shareholders' agents), and therefore the payment scheme between them will be designed to mitigate these problems. The conflict of interest between shareholders and managers (such as the free cash flow problem) causes the board of directors (shareholders) to design managerial compensation schedules which are dependent upon a committed payment out of the firm. This paper argues that greater flexibility allowed by a compensation scheme based on dividends instead of debt leads to a preference for dividends in alleviating this agency problem. When management is also better informed as to the value of the firm (determined by the present value of future cash flows), and shareholders desire this value to be conveyed, then the committed payment can serve as a natural signal to alleviate this adverse selection problem. A major reason that no answer has been found to the dividend puzzle is that the objective function of the agents paying dividends has not been adequately modeled. It is shown here, however, that in many circumstances contracts based upon dividend payments can provide a simultaneous solution to both problems, whereas contracts based upon debt cannot. Thus, dividends may have an advantage over debt in alleviating the free cash flow type problems and that the legal force associated with debt may not be required. The contribution to the dividend puzzle literature is that an explanation is provided of why debt or retained earnings are not substituted for dividends
Keywords: 330